Sustainability Model for Private Higher Education of North Sumatra Indonesia - Haniza Haniza; Nazaruddin Matondang; Juliza Hidayati (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2021)
The sustainability of private higher education depends on the adaptive competence that universities apply in facing global challenges. This research developed an integrated sustainability model of managing higher education which used the local and global challenges to face the competitiveness in handling higher education. With a Research and Development Model, this study offered a sustainability strategy that includes dimensions; education and research, community involvement, operation, and administration. Data found that many higher education institutions in Medan Municipality of North Sumatra face human resources problems; the majority of private universities only have less than 10 percent hold a doctoral degree and most of their working time doing teaching and administration tasks, but the low publication of research. The sustainability of private universities in Medan Municipality of North Sumatra Province mostly was found in threat conditions due to the lack of an integrated model that could adapt to global challenges. This model recommends the private universities build an integrated model which changes the workloads of lecturers to be research-oriented.